Half-sweep modified successive overrelaxation for solving two-dimensional Helmholtz equations - M.K.M Akhir; M. Othman; Jumat.Sulaiman; Z.A Majid; M. Suleiman (INSInet Publications, 2011)
The main purpose of this article is to examine the effectiveness of the Half-sweep Modified Successive OverRelaxation (HSMSOR) in solving the sparse linear systems generated form discretization of the two-dimensional Helmholtz equations. In addition, the application and formulation of the HSGS iterative method also presented. Some illustrative examples are given to point out the efficiency of the proposed method.